An examination of the correlation amongst trunk flexibility, x-factor and clubhead speed in skilled golfers - Joyce, C. (Journal of Sports Sciences, 2017)
Skilled golfers are reported to be more flexible than lesser able golfers, which may assist in increased x-factor (shoulder-pelvis separation) at the top of the backswing. However, it is unknown if increased flexibility produces faster clubhead speed. The aim of this study was to investigate the correlations amongst trunk flexibility and x-factor, as well as the association between flexibility and clubhead speed in low handicap golfers. Fifteen low handicap male golfers who displayed a modern swing, had their trunk static anatomical end-range of motion (flexibility) and driver swing kinematics were measured. Although Pearson correlations revealed trunk extension and lateral bending were moderately related to x-factor, axial rotation flexibility was not. A generalised linear model (GLM) reported three axial rotation flexibility variables, and six golf swing kinematic variables were associated with faster clubhead speed. The Pearson correlation results suggest that skilled golfers who have increased axial rotation flexibility do not necessarily utilise it to increase x-factor, and the GLM results support the importance of multisegment flexibility and interaction for improving golf performance with skilled golfers.